Eye Movement Analysis and Cognitive Assessment - Rosa, Pedro J.; Gamito, Pedro; Oliveira, Jorge; Morais, Diogo; Pavlovic, Matthew; Smyth, Olivia; Maia, Inês; Gomes, Tiago (Methods of Information in Medicine, 2017)
Background: An adequate behavioral response depends on attentional and mnesic processes. When these basic cognitive functions are impaired, the use of non-immersive Virtual Reality Applications (VRAs) can be a reliable technique for assessing the level of impairment. However, most non-immersive VRAs use indirect measures to make inferences about visual attention and mnesic processes (e.g., time to task completion, error rate).Objectives: To examine whether the eye movement analysis through eye tracking (ET) can be a reliable method to probe more effectively where and how attention is deployed and how it is linked with visual working memory during comparative visual search tasks (CVSTs) in non-immersive VRAs.Methods: The eye movements of 50 healthy participants were continuously recorded while CVSTs, selected from a set of cognitive tasks in the Systemic Lisbon Battery (SLB). Then a VRA designed to assess of cognitive impairments were randomly presented.Results: The total fixation duration, the number of visits in the areas of interest and in the interstimulus space, along with the total execution time was significantly different as a function of the Mini Mental State Examination (MMSE) scores.Conclusions: The present study demonstrates that CVSTs in SLB, when combined with ET, can be a reliable and unobtrusive method for assessing cognitive abilities in healthy individuals, opening it to potential use in clinical samples.
Keywords: Eye movements; attention; memory; virtual reality; comparative visual search task